Students’ Perception toward the Merdeka Belajar Kampus Merdeka Policy (Case Study at a Private University in South Tangerang) - CITRANINGTYAS, Clara Evi C.; SETIWAN, Agustinus Agus; PURWANTO, Dr. Edi (CENTRAL ASIA AND THE CAUCASUS, 2021)
This research presents a case study of students' perceptions, comprehension, and interest in the "Merdeka Belajar Kampus Merdeka" (MBKM) or freedom to learn program. The goal of this research is to acquire an understanding of students' comprehension, experience, interests, challenges, satisfaction, criticism, and suggestions concerning the MBKM program at a private university in South Tangerang, Indonesia. The Focus Group Discussion (FGD) approach was used to collect student opinions from 78 students across 10 undergraduate programs, including science and social humanities. Respondents were chosen through purposeful sampling. According to the data, students are generally interested in participating in the MBKM program but lack a comprehensive information of it. The most significant challenge they encounter is a lack of socialization. Students' comments and recommendations provide promise for improved and more clear socialization and information. This insight has the potential to improve the program.